Isolated congenital asplenia: An overlooked cause of thrombocytosis. Issue 8 (17th March 2022) - Borsani, Oscar; Asano, Takaki; Boisson, Bertrand; Fraticelli, Sara; Braschi‐Amirfarzan, Marta; Pietra, Daniela; Casetti, Ilaria Carola; Vanni, Daniele; Trotti, Chiara; Borghesi, Alessandro; Casanova, Jean‐Laurent; Arcaini, Luca; et al.
Abstract :